2005
DOI: 10.1901/jeab.2005.82-04
|View full text |Cite
|
Sign up to set email alerts
|

THE ROLE OF DOPAMINE IN REINFORCEMENT: CHANGES IN REINFORCEMENT SENSITIVITY INDUCED BY D1-TYPE, D2-TYPE, AND NONSELECTIVE DOPAMINE RECEPTOR AGONISTS

Abstract: Dose-dependent changes in sensitivity to reinforcement were found when rats were treated with low, moderate, and high doses of the partial dopamine D1-type receptor agonist SKF38393 and with the nonselective dopamine agonist apomorphine, but did not change when rats were treated with similar doses of the selective dopamine D2-type receptor agonist quinpirole. Estimates of bias did not differ significantly across exposure to SKF38393 or quinpirole, but did change significantly at the high dose of apomorphine. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Perseverative, time-consuming, excessive, and rigid are thus features fully disclosed in the QNP-induced CFL model, besides being terms recurrent in the literature concerning obsessive-compulsive disorder (OCD). Our findings are consistent with previous reports demonstrating that repeated administrations of QNP produce repetitive checking (Szechtman et al 1998), perseverative operant responding in the absence of reward (Kurylo 2004), enhancement of the excessive lever pressing in condition of post-training signal attenuation (Joel and Avisar 2001), focusing on the response lever throughout the operant conditioning session (Bratcher et al 2005). Thus, regardless of the ethological significance of the specific behavior involved, QNP appears to be a valid tool in the study of animal models of OCD.…”
Section: Introductionsupporting
confidence: 92%
“…Perseverative, time-consuming, excessive, and rigid are thus features fully disclosed in the QNP-induced CFL model, besides being terms recurrent in the literature concerning obsessive-compulsive disorder (OCD). Our findings are consistent with previous reports demonstrating that repeated administrations of QNP produce repetitive checking (Szechtman et al 1998), perseverative operant responding in the absence of reward (Kurylo 2004), enhancement of the excessive lever pressing in condition of post-training signal attenuation (Joel and Avisar 2001), focusing on the response lever throughout the operant conditioning session (Bratcher et al 2005). Thus, regardless of the ethological significance of the specific behavior involved, QNP appears to be a valid tool in the study of animal models of OCD.…”
Section: Introductionsupporting
confidence: 92%
“…Therefore, this QNPinduced behavior appears to be a complex phenomenon where exaggerated responding coexists with dissociation between the appetitive and consummatory components of water-reinforced behavior. It is not surprising that under our experimental conditions, QNP induced exaggerated responding in that the drug increased the excessive lever pressing obtained by post-training signal attenuation (Joel et al 2001), elicited perseverative operant responding in the absence of reward (Kurylo 2004), caused rats trained to respond for food to remain focused on the response lever throughout the operant conditioning session (Bratcher et al 2005), and induced repetitive checking of specific places . From an economic point of view, QNP-induced CFL appears quite dissipative, since under these conditions the animals work for a resource that they only partially use and which, in any case, they can have for free.…”
Section: Introductionmentioning
confidence: 81%
“…Joel et al (2001) found that QNP further increases the excessive lever pressing induced by posttraining signal attenuation, whereas Kurylo (2004) found that the drug elicits perseverative operant responding in the absence of reward. Finally, Bratcher et al (2005) observed that upon QNP administration rats trained to respond for food remained focused on the response lever for the entire operant conditioning session, whereas the selective D1 agonist, SKF 38393, increased locomotion and sniffing in the operant cage. Perseveration of responding in the choice phase of the experiment led QNP-treated rats to gain many more rewards than vehicle-treated controls (Fig.…”
Section: Appetition Consumption and Motivationmentioning
confidence: 96%
“…Besides compulsive checking, quinpirole administration produces other perseverative, time-consuming, excessive, and rigid behaviors such as perseverative operant responding in the absence of reward, 87 enhancement of excessive lever-pressing in the condition of post-training signal attenuation, 88 and focusing on the response lever throughout the operant conditioning session. 89 Intrastriatal injections of quinpirole elicit perseverative non-rewarded instrumental responses, 90 whereas intra-accumbens injections of the drug cause a general impairment of flexibility in a reversal learning task. 91 Quinpirole thus appears to reduce behavioral flexibility in coping with environmental stimuli by exaggerating adaptive strategies, which is in line with proposed models of OCD.…”
Section: Leading Animal Models Of Ocdmentioning
confidence: 99%